Junior High School Students' Mathematics Problem-Solving Ability Using the Problem-Based Learning Model: A Systematic Review - Hanifah, Hanifah; Mutmainah, Siti; Kartika, Hendra (Journal of Research in Science and Mathematics Education, 2024)
Purpose: This study aims to examine the ability of junior high school students to solve mathematical problems through the application of the Problem-Based Learning (PBL) model. Methodology: The research method used in this study is a systematic literature review. Researchers searched for journal articles on junior high school students' mathematical problem-solving ability using the Problem-Based Learning model. The search was conducted through the Google Scholar database, and the Publish or Perish application was used. Findings: Based on the analyzed articles, it can be concluded that the Problem-Based Learning model improves students' mathematical problem-solving skills. This is supported by the increase in students' skills before and after implementation. Significance: This research is expected to serve as a reference for teachers and researchers interested in improving mathematical problem-solving skills using the Problem-Based Learning model.